2017
DOI: 10.1016/j.jsbmb.2016.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously produced nonclassical vitamin D hydroxy-metabolites act as “biased” agonists on VDR and inverse agonists on RORα and RORγ

Abstract: The classical pathway of vitamin D activation follows the sequence D3→25(OH)D3→1,25(OH)2D3 with the final product acting on the receptor for vitamin D (VDR). An alternative pathway can be started by the action of CYP11A1 on the side chain of D3, primarily producing 20(OH)D3, 22(OH)D3, 20,23(OH)2D3, 20,22(OH)2D3 and 17,20,23(OH)3D3. Some of these metabolites are hydroxylated by CYP27B1 at C1α, by CYP24A1 at C24 and C25, and by CYP27A1 at C25 and C26. The products of these pathways are biologically active. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 126 publications
(162 citation statements)
references
References 105 publications
(170 reference statements)
12
149
0
1
Order By: Relevance
“…VDR expression was identified in many tissues and cells, including epidermal and dermal skin cells that both synthesize 1,25(OH) 2 D 3 (calcitriol) and respond to it (10,107,(113)(114)(115). Noncanonical, noncalcemic hydroxylated vitamin D 3 forms (9, 30, 33) can also act on VDR (116)(117)(118)(119). They can also act as inverse agonists on retinoic acid-related orphan receptors (RORs) α and γ (117,120), which are expressed in normal and pathological skin cells, including melanoma (120,121).…”
Section: Classical and Non-classical Vitamin D Derivativesmentioning
confidence: 99%
“…VDR expression was identified in many tissues and cells, including epidermal and dermal skin cells that both synthesize 1,25(OH) 2 D 3 (calcitriol) and respond to it (10,107,(113)(114)(115). Noncanonical, noncalcemic hydroxylated vitamin D 3 forms (9, 30, 33) can also act on VDR (116)(117)(118)(119). They can also act as inverse agonists on retinoic acid-related orphan receptors (RORs) α and γ (117,120), which are expressed in normal and pathological skin cells, including melanoma (120,121).…”
Section: Classical and Non-classical Vitamin D Derivativesmentioning
confidence: 99%
“…9496 Thus, in addition to the well-established mechanism of activation by binding of active forms of vitamin D to the genomic site of the VDR, there are non-genomic membrane-associated sites of action (A-VDR and 1,25D3-MARRS) as well as other nuclear receptor targets comprising ROR- α and -γ . 95 The regulatory targets for pD and aD secosteroids or lumisterol compounds remain to be identified.…”
Section: Vitamin D In a ‘Nutshell’mentioning
confidence: 99%
“…NRs, highly conserved transcription factors, regulate a variety of biological processes under normal and pathological conditions, including cell differentiation, immune response, circadian rhythm, lipid, steroid, xenobiotic and glucose metabolism, (reviewed in). Vitamin D receptor (VDR) are targets for bioregulatory functions of 1,25(OH) 2 D3 and novel CYP11A1 derived vitamin D‐hydroxyderivatives in skin cancers. In addition, vitamin D and lumisterol hydroxyderivatives can act on RORα, RORγ as inverse agonists and CYP11A1‐derived vitamin D metabolites also act as agonists on aryl hydrocarbon receptor (AhR) .…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D receptor (VDR) are targets for bioregulatory functions of 1,25(OH) 2 D3 and novel CYP11A1 derived vitamin D‐hydroxyderivatives in skin cancers. In addition, vitamin D and lumisterol hydroxyderivatives can act on RORα, RORγ as inverse agonists and CYP11A1‐derived vitamin D metabolites also act as agonists on aryl hydrocarbon receptor (AhR) . Recently, several studies showed that the expression of VDR could be regulated by hypoxia .…”
Section: Introductionmentioning
confidence: 99%